2019
DOI: 10.1139/cjpp-2018-0691
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP21 deficiency impairs hepatic lipid metabolism and improves insulin signaling in lean and obese mice

Abstract: ARHGAP21 is a Rho-GAP that controls GTPases activity in several tissues, but its role on liver lipid metabolism is unknown. Thus, to achieve the Rho-GAP role in the liver, control and ARHGAP21-haplodeficient mice were fed chow (Ctl and Het) or high-fat diet (Ctl-HFD and Het-HFD) for 12 weeks, and pyruvate and insulin tolerance tests, insulin signaling, liver glycogen and triglycerides content, gene and protein expression, and very-low-density lipoprotein secretion were measured. Het mice displayed reduced body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…ARHGAP21 heterozygotes mice presented an increased expression of UCP1 in BAT (Brown Adipose Tissue) (8), and increased of SREBP-1C and ACC gene expression in liver. In addition, these mice presented a reduction in CPT1a gene expression in liver (9). Therefore, based on this, we are tempted to speculate that ARHGAP21 also may affect lipids metabolism in pancreatic bcells and consequently reduces insulin secretion.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…ARHGAP21 heterozygotes mice presented an increased expression of UCP1 in BAT (Brown Adipose Tissue) (8), and increased of SREBP-1C and ACC gene expression in liver. In addition, these mice presented a reduction in CPT1a gene expression in liver (9). Therefore, based on this, we are tempted to speculate that ARHGAP21 also may affect lipids metabolism in pancreatic bcells and consequently reduces insulin secretion.…”
Section: Discussionmentioning
confidence: 93%
“…• For experiments involving hypo insulin-secreting mice: [8][9][10][11][12] weeks old male Swiss mice, acquired from the State University of Campinas, were maintained on a 12 h light-dark cycle at 20-21°C, with controlled humidity during the entire experiment and fed with a standard CHOW diet and offered tap water ad libitum. Mice were randomly assigned to a sedentary control group (CTL), which limited to typical movement inside the cages, and the endurance-training group (T).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the upregulated DEGs, ARHGAP21 was the only gene whose expression was found significantly positively related to both patient OS and DFS. ARHGAP21 functions preferentially as a GTPase-activating protein (GAP) for CDC42 and regulates the ARP2/3 complex and F-actin dynamics at the Golgi through control of CDC42 activity 26 . Evidence showed that as a PDZ domain containing protein, ARHGAP21 could interact with the PDZ-binding motif of Claudin-2, in such way promoted breast cancer liver metastasis 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described 33 . Briefly, hypothalamus and BAT samples were homogenized in lysis buffer and centrifuged (12,000 g for 20 min at 4 °C) to obtain a protein extract.…”
Section: Methodsmentioning
confidence: 99%